PERAN ASEAN DALAM MENANGGULANGI TINDAK PIDANA TERORISME DI KAWASAN ASIA TENGGARA TAHUN 2011-2014 - Khairizky, Said Khairizky; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes the rules of ASEAN to counter the terorism in South Asea Region in 2011-2014. The terorism are the act of threat the public society. South Asea region are one of the increase terorism group. Indonesia, Malaysia, Singapore and Filiphina are the state in South Asea region that be place a terorism group act.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the rules of ASEAN to counter the terorism in South Asea Region. The theories applied in this research are international organization suchs as regional organization theory from Clive Archer and concept defenition from terorism.The research shows that the rules of ASEAN to handled the terorism in South Asea Region are create the Asean Regional Forum and ASEAN Convention On Counter Terrorism with in 2011 Asean Regional Forum create a annual Senior Officials Meeting in Transnational Crime, in 2011 state of ASEAN dealed about ASEAN Convention On Counter Terrorism and ASEAN create agreement with United States and European Union to counter on terorism.Key words: rule, ASEAN, counter, terorism.